Self‐Contained Handheld Magnetic Platform for Point of Care Cytometry in Biological Samples. Issue 9 (6th October 2016) - Yenilmez, Bekir; Knowlton, Stephanie; Tasoglu, Savas
Abstract : Magnetic levitation is a powerful tool capable of distinguishing micrometer‐scale particles based on their densities. When a particle is suspended in a paramagnetic medium and placed in a magnetic field formed by two permanent magnets with like poles facing each other, the particle will experience two forces—a magnetic force and a buoyant force. These forces cause a particle, such as a cell, which does not necessarily have magnetic properties, to levitate at a height inversely proportional to its density. Magnetic levitation has been shown to be useful for a range of applications, including disease diagnostics, material characterization, and quality control. Here, a portable, self‐contained device fully independent from a dedicated microscope or smartphone is developed to levitate particles of interest, image them using an embedded low‐cost optical system and a camera module, and process the captured images in order to estimate the densities of the particles. The device is user‐friendly and inexpensive, offering a great potential for rapid, on‐site sample analysis such as white blood cell cytometry. Abstract : The low‐cost, handheld, and user‐friendly standalone device shown here is developed based on magnetic levitation technology, which uses magnets to separate particles, such as cells, based on their densities. Automated imaging and analysis is performed on‐board to analyze the density distribution, which can be used for a range of medical diagnostics on‐site such as white blood cell cytometry.